Culturally Responsive Counseling Practices in Senior and Vocational High Schools: A Systematic Literature Review - Priska Diana Lisa; Lidia Jelaus; Amelia Juloma Mboes (Journal of Psychology and Education Counseling (JPEC), 2026)
This study aimed to identify and analyze the implementation of culturally responsive counseling in senior high schools and vocational high schools in Indonesia. A systematic literature review was conducted using studies retrieved from Google Scholar and the Garuda database. The initial search identified 10 potentially relevant studies, of which four met the predetermined inclusion criteria and were included in the analysis. The main inclusion criteria comprised studies published between 2016 and 2026 that examined the implementation or development of counseling approaches integrating Indonesian cultural values at the senior or vocational high school level. Studies conducted at other educational levels or published before 2016 were excluded. The findings revealed that several local cultural values had been integrated into individual and group counseling services, including Sasak culture, Masohi values, Acehnese Panton, and Javanese cultural values. These cultural elements were incorporated into counseling models and interventions combined with techniques such as focus group discussions and the person-centered approach. Development studies generally reported that the culturally based counseling products were feasible for use in school counseling services. Meanwhile, an experimental study integrating Masohi cultural values reported a significant reduction in bullying behavior. These findings highlight the potential of integrating local cultural values into counseling services to support culturally responsive and contextually relevant practices in Indonesian secondary schools.